Metabolomics flux introduction - Cascante, Marta; Marín de Mas, Igor (Henry Stewart Talks, 2018)
Recent approaches in system biology and modeling, Different compartment and building of genome scale metabolic network models, Using system biology markup languages (SBML) to represent metabolic models, Main concepts in SBML model building